Increasing The Effectiveness And Efficiency Of Local Msme Consignment Cooperation With The Vendor System - Fredy Rizaldi; Agus Munandar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
MSMEs have an important role in the Indonesian economy but face challenges in adapting to the digital era and establishing effective collaboration with retail companies. This research aims to develop and evaluate a vendor portal system that can overcome this challenge by increasing the effectiveness and efficiency of consignment collaboration between local MSMEs and retail companies. Using qualitative descriptive methods, this research analyzes the impact of implementing a vendor portal system on consignment business processes, including operational efficiency, transparency, and collaboration between both parties. The research results show that the vendor portal system has succeeded in increasing operational efficiency, providing real-time transparency of sales and inventory data, and facilitating better communication between MSMEs and retail companies. Apart from that, this system also supports government programs in encouraging MSMEs to "Go Digital" and "Upgrade"